Desire for hastened death: how do professionals in specialized palliative care react?†. Issue 5 (16th September 2015) - Galushko, M.; Frerich, G.; Perrar, K. M.; Golla, H.; Radbruch, L.; Nauck, F.; Ostgathe, C.; Voltz, R.
Abstract: Objective: Desires for hastened death (DHD; wish to hasten death is also in use) are prevalent in terminally ill patients. Studies show that health professionals (HP) are often underprepared when presented with DHD. HPs in specialized palliative care (SPC‐HP) often encounter DHD. This study aimed to identify SPC‐HP responses to DHD in daily practice and their corresponding functions. Methods: Narrative interviews were conducted with 19 SPC‐HPs at four German University Hospitals. Transcripts were analyzed using the documentary method. An inventory of established responses to DHD was compiled, and their corresponding functions in the context of the patient–SPC‐HP interaction were reconstructed. Results: Twelve response categories and six corresponding functions were identified. On the patient level, responses categorized as symptom control, exploring the reasons and generating perspective, reorientation, and hope were particularly used to ease the patient's burden. On the interaction level, creating a relationship was fundamental. On the SPC‐HP level, various methods served the functions self‐protection and showed professional expertise. Conclusions: Profound personal and professional development is necessary to respond to the inherent challenges presented by DHD. Establishing helpful relationships with patients is essential regardless of SPC‐HP specialization. SPC‐HPs should maximize their skills in establishing and maintaining relationships as well as strengthening their own resilience, possibly in specific training courses. Copyright © 2015 John Wiley & Sons, Ltd.